Gabriel Falloppius (1523–1562) and the facial canal. Issue 1 (1st April 2013) - Macchi, Veronica; Porzionato, Andrea; Morra, Aldo; De, Raffaele
<x xml:space="preserve">Abstract</x> Gabriel Falloppius is known for his contributions to anatomy. Indeed, many anatomic structures bear his name, such as the Fallopian tubes, and his descriptions often contradicted those of other notable anatomists, such as Galen and Andreas Vesalius. In his textbook "Observationes Anatomicae, " he described for the first time the structures of the ear, eye, and female reproductive organs, and elucidated the development of the teeth. Furthermore, Falloppius described the facial canal. The objectives of this paper are to provide an overview of Falloppius's life and to discuss the clinical relevance of the facial canal as understood from his description of this anatomic structure. Clin. Anat. 27:4–9, 2014. © 2013 Wiley Periodicals, Inc.